Continuing education of teachers in Basic Education: a systematic review (Research, Society and Development, 2022)
This article presents a systematic review of the literature on the processes of continuing education of teachers working in Basic Education. The objective is attenuated in articulating and substantiating the theoretical foundations laid out in the literature in the face of the didactic-pedagogical contributions provided by continuing education in the stages of Basic Education. By opening the context, the pandemic crisis is justified as an 'awakening' of continuing education with an emphasis on digital technologies. In the pandemic, a romanticization of face-to-face teaching was identified and, such a modality is understandable as an enhancer of many teaching and learning activities, however, many of the shortcomings evidenced in the pandemic are reflections of years of teaching devaluation that occurred even in face-to-face teaching. In view of this, it is necessary to encourage the updating of teachers in training courses, events, lectures, seminars, lives, among other means of going beyond training / performance. Entering the results, this research shows that school management must seek training subsidies for teachers, the Public Education Network must promote resources for training and updating teachers as an incentive to improve their teachers, innovating in knowledge, therefore, the value of this articulation will result in improvements in the teaching and learning process of Basic Education students.